Statin-use and perceptions of high cholesterol as predictors of healthy lifestyle behaviours in Nigerians - Joyce F. Coker; Kate M. Hill; Akaninyene A. Otu; Allan House (Public Library of Science (PLoS), 2022)
It is unclear how statin-use influences the adoption of healthy lifestyle choices. It is important to understand the nature of this relationship as this could facilitate targeted public health interventions which could help promote a healthy lifestyle, curb the rise of non-communicable diseases, and facilitate overall health. This study aimed to explore whether statin-use influenced the adoption of healthy lifestyle choices by changing the way urban and semi-urban Nigerians thought about their high cholesterol and their future risk of cardiovascular disease. Structured questionnaires were used to compare the lifestyle behaviours, perceptions of high cholesterol and future risk of cardiovascular disease of statin users and non-statin users recruited in urban and a semi-urban Nigeria. In-depth, face-to-face interviews were used to further explore the relationship between statin-use and the adoption of healthy lifestyle choices, and explore the influence of personal and social factors on this relationship. The odds of adopting a low-fat diet increased as perceived statin-effectiveness increased (OR = 2.33, p<0.05), demonstrating a synergistic relationship between statin-use and the adoption of healthy of lifestyle choices. In addition to this synergistic association, at interview, two other relationships were found between statin use and the adoption of healthy lifestyle choices: an antagonistic relationship fuelled by a strong perception of statin effectiveness and a perceived inability to make healthy lifestyle changes, which favoured statin-use, and an antagonistic relationship fuelled by congruous cause-control beliefs and concerns about medication-use which favoured the adoption of healthy lifestyle choices. The odds of adopting a low-fat diet was 5 times greater in urban dwellers than in semi-urban dwellers (p<0.01). Statin-use influenced the adoption of healthy lifestyle choices in three different ways, which require exploration at clinical consultation. Gender, social obligations, and physical environment also influenced statin-use and the adoption of healthy lifestyle choices.